Enhancing Student Creativity through Project Based Learning in Indonesia’s National Curriculum - Pratama, Yoga (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2025)
This study examines the impact of Project Based Learning (PjBL) on student creativity within the National Curriculum at elementary schools. Using a quantitative experimental design, the study involved two groups: the experimental group applying PjBL and the control group following conventional learning methods. The sample consisted of 120 fifth grade students divided into these two groups. Data were collected through a validated creativity test administered before and after the intervention. The results revealed that the experimental group showed a significant increase in creativity compared to the control group. The average creativity score for the experimental group rose from 62.5 to 85.3, whereas the control group only increased from 61.4 to 65.2. These results demonstrate that implementing PjBL in the National Curriculum effectively enhances student creativity, particularly in problem-solving, originality of ideas, and collaboration skills. Consequently, PjBL can serve as a valuable method for fostering 21st-century skills, which align with the core objectives of Indonesia’s National Curriculum.